2022
DOI: 10.1038/s41598-022-13060-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Neuromedin B does not alter body weight and glucose homeostasis nor does it act as an insulin-releasing peptide

Abstract: Neuromedin B (NMB) is a member of the neuromedin family of neuropeptides with a high level of region-specific expression in the brain. Several GWAS studies on non-obese and obese patients suggested that polymorphisms in NMB predispose to obesity by affecting appetite control and feeding preference. Furthermore, several studies proposed that NMB can act as an insulin releasing peptide. Since the functional study has never been done, the in vivo role of NMB as modulator of weight gain or glucose metabolism remai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Neuromedin B and its receptor are highly expressed in AT. Cikes et al suggested that neuromedin B does not change body weight and glucose homeostasis on a standard diet nor acts as an insulin‑releasing peptide [ 164 ]. Neuromedin B receptor disruption impairs adipogenesis in mice and 3T3-L1 cells.…”
Section: Secretory Factors Of Brown/beige Adipocytes: Endocrine Parac...mentioning
confidence: 99%
“…Neuromedin B and its receptor are highly expressed in AT. Cikes et al suggested that neuromedin B does not change body weight and glucose homeostasis on a standard diet nor acts as an insulin‑releasing peptide [ 164 ]. Neuromedin B receptor disruption impairs adipogenesis in mice and 3T3-L1 cells.…”
Section: Secretory Factors Of Brown/beige Adipocytes: Endocrine Parac...mentioning
confidence: 99%